(3QSGdI aj edGReI Mce GdYbd eY GdTQYs - (3ejQRG CHh GdbGSe cdGfJQs
(3ChdgG (B:s
(3hjJe GdcdGe ajg ai CUhd JMOjO YQa GdOdjd GdYbdi s
(3BNQgG (B:s
(3eKd gPG GdMSf hGdbHM ai GdCeQ hGdfgi dCfg ai bhI GdNGQL s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdSGHYIs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(130) s
Keywords: (3GdadSaI hGdefWbs